1985
DOI: 10.1126/science.3925555
|View full text |Cite
|
Sign up to set email alerts
|

Neurovisceral and Skeletal G M1 -Gangliosidosis in Dogs with β-Galactosidase Deficiency

Abstract: Beta-galactosidase-deficient siblings in two litters of English springer spaniel puppies showed a progressive neurological impairment, dwarfism, orbital hypertelorism, and dysostosis multiplex. An excess of GM1-ganglioside was found in the brain. Three abnormal oligosaccharides were present in samples of urine, brain, liver, and cartilage. Light microscopy of selected tissue specimens revealed cytoplasmic vacuoles in neurons, circulating blood cells, macrophages, and chondrocytes. Ultrastructural studies demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…The fact that no other structure comparable in size with the MLBs is present in the transfected cells identifies the large fluorescently labeled LAMP-2-and L-PHA-positive vacuoles as MLBs. Deficiency in lysosomal galactosidases and sialidases is associated with the accumulation of lamellar bodies, demonstrating that impaired lysosomal degradation of glycoproteins or glycolipids can be associated with the formation of lamellar bodies (Amano et al, 1983;Alroy et al, 1985;Allegranza et al, 1989;Ohshima et al, 1997).…”
Section: Role Of Lysosomal Degradation In Mlb Biogenesismentioning
confidence: 99%
“…The fact that no other structure comparable in size with the MLBs is present in the transfected cells identifies the large fluorescently labeled LAMP-2-and L-PHA-positive vacuoles as MLBs. Deficiency in lysosomal galactosidases and sialidases is associated with the accumulation of lamellar bodies, demonstrating that impaired lysosomal degradation of glycoproteins or glycolipids can be associated with the formation of lamellar bodies (Amano et al, 1983;Alroy et al, 1985;Allegranza et al, 1989;Ohshima et al, 1997).…”
Section: Role Of Lysosomal Degradation In Mlb Biogenesismentioning
confidence: 99%
“…3. 28 [4][5][6][7][8][9] was counted using air-dried blood smears stained with May-Grünwald-Giemsa. Ophthalmologic examination and cerebrospinal fluid (CSF) analysis were performed and skeletal radiographs were obtained for dog Nos.…”
Section: Case Historiesmentioning
confidence: 99%
“…38 The disease has been described in a variety of species, including cats, cattle, sheep, mice, and humans. [1][2][3][4][5][6][7][8][9]12,14,16,17,[27][28][29]31,[33][34][35][36][37][38] Until now, the canine form has been found in English Springer Spaniels (ESS), 3,33 Portuguese Water Dogs (PWD), 3,35,36 mixed-breed Beagles, 34 and Alaskan Huskies. 28 In humans, the disorder is classified as infantile (type 1), juvenile (type 2), and adult (type 3) forms.…”
mentioning
confidence: 99%
“…Similarly, neural stem cells isolated from adult human olfactory bulb biopsies contained self-renewing, multipotential neural stem cells as evidenced by clonal analysis (Pagano et al, 2000). Many neurologic diseases that may potentially benefit from NPC transplantation occur in the dog (Griffiths et al, 1981;Haskins et al, 1984;Alroy et al, 1985;Koppang, 1988;Fischer et al, 1998;Wenger et al, 1999). We recently found that defects in canine NPCs occur in a model of a lysosomal storage disease (Walton and Wolfe, 2007).…”
Section: Introductionmentioning
confidence: 99%